2017
DOI: 10.1016/j.aott.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of short term radiological alignment outcomes of the patient specific and standard instrumentation for primary total knee arthroplasty: A systematic review and meta-analysis

Abstract: ObjectiveThe aim of this study was to review the radiological alignment outcomes of patient Specific (PS) cutting blocks and Standard Instrumentation in Primary Total Knee Arthroplasty.MethodsWe hypothesized that the use of PS techniques would significantly improve sagittal, coronal and rotational alignment of the prosthesis on short term. We performed a systematic review and a meta-analysis including all the randomised controlled trials (RCT) using PS and standard (ST) total knee arthroplasty to date.ResultsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…More studies and longer follow-up period are needed to make definitive conclusions about the PSI efficacy and the potential applicability of PSI to special situations. A similar study by Alcelik et al [ 6 ] showed that PSI is not superior to ST instrumentation in primary total knee arthroplasty.…”
Section: D Printed Patient-specific Instrumentationmentioning
confidence: 83%
See 1 more Smart Citation
“…More studies and longer follow-up period are needed to make definitive conclusions about the PSI efficacy and the potential applicability of PSI to special situations. A similar study by Alcelik et al [ 6 ] showed that PSI is not superior to ST instrumentation in primary total knee arthroplasty.…”
Section: D Printed Patient-specific Instrumentationmentioning
confidence: 83%
“…There are 336 papers available through a PUBMED search (revised September 25, 2017) using the query “Total knee replacement/arthroplasty” and “patient specific instrumentation.” However, there are 68 papers available through a PUBMED search (revised September 25, 2017) using the query “Total knee replacement/arthroplasty” and “customized.” Among these 68 papers, 28 papers are relevant to the knee replacement and patient-specific instrumentation (PSI) or implant designs. There were recent review papers on PSI by Rodrigues and Gutierres [ 5 ] and Alcelik et al [ 6 ]; therefore, this paper will focus on customized TKR implants and musculoskeletal (MSK) modelling of knee joint. Relevant papers searched from ScienceDirect (Elsevier) were also reviewed for the development of customized TKR.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a recent meta-analysis involving 2866 knees operated on with patient-specific instruments and 2956 knees with conventional instruments from 44 clinical studies, it was reported that patient-specific instrumentation improved the accuracy of femoral component alignment and global mechanical alignment, but increased tibial component malalignment [ 18 ]. In another recent meta-analysis comparing 538 cases of patient-specific and 549 cases of conventional instrumentation for TKA, patient-specific cutting guides had no superiority in the sagittal positioning of either the tibial or femoral components, and even worse sagittal plane tibial component positioning [ 11 ]. In the present study, cTCA was 88.8°±0.9° and cFCA was 95.2°±1.6° on postoperative radiographs, showing good postoperative mechanical and anatomical alignment, particularly for the femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient-specific instruments have been used for TKA to be more efficient and cost-effective, many studies have shown controversial and inconsistent results on the efficiency and accuracy of TKA performed by using patient-specific cutting guides, mostly due to various 3D guide construction techniques or outcome measures that were used in the studies [ 1 ]. As most of the individual clinical studies reported the superiority of patient-specific instrumentation over conventional methods for providing limb alignment [ 2 , 10 ], meta-analyses failed to show significant difference between the 2 techniques [ 1 , 11 ]. In order to increase decisive evidence on the benefits and disadvantages of this innovative technique, more clinical studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a new technology that could reduce the proportion of incorrectly aligned implants appears appealing. However, there is controversy in the available published literature on the ability of PSI to affect the implant positioning, with some studies showing increased accuracy of femoral rotation with the use of PSI [8][9][10][11] and others revealing no differences from conventional alignment techniques [12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%